2015
DOI: 10.1515/vzoo-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

New Data on the Morphology and Distribution of Oswaldocruzia Skrjabini (Nematoda, Molineidae)

Abstract: Sixteen specimens of Oswaldocruzia (Nematoda, Molineidae) were found in the material from Zootoca vivipara Lichtenshtein, 1823 collected in Ukraine. The nematodes were identified as O. skrjabini Travassos, 1937 due to the presence of well-developed cervical alae and the host species. Based on the specimens examined, an amended description of the species, with new morphological characters and metrical data, was composed; its distribution in Ukraine was outlined. Oswaldocruzia skrjabini differs from other specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…The molecular phylogenetic analysis also showed that Oswaldocruzia nematodes collected in this study from different species of amphibians and reptiles in European Russia belonged to the species Oswaldocruzia filiformis s.l. Thus, our data contradict the opinion that several species of this genus parasitise different host species in the Western Palearctic (Durette-Desset et al, 1993;, 1995Svitin, 2015Svitin, , 2016Svitin, , 2017.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…The molecular phylogenetic analysis also showed that Oswaldocruzia nematodes collected in this study from different species of amphibians and reptiles in European Russia belonged to the species Oswaldocruzia filiformis s.l. Thus, our data contradict the opinion that several species of this genus parasitise different host species in the Western Palearctic (Durette-Desset et al, 1993;, 1995Svitin, 2015Svitin, , 2016Svitin, , 2017.…”
Section: Discussioncontrasting
confidence: 88%
“…On the contrary, in Oswaldocruzia bialata and O. duboisi, the blade is sharp at the end and not divided into branches Durette-Desset et al, 1993;Svitin & Kuzmin, 2012;Svitin, 2016). Oswaldocruzia skrjabini has extra branches on the «fork» and the «shoe», and the blade is divided at the end into four branches (Svitin, 2015). In our study, all nematodes have an additional branch on each ray 10, which is also present in Oswaldocruzia skrjabini, but not found in O. filiformis, O. bialata and O. duboisi.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations